Artificial bacterial degradation and hydrous pyrolysis of suberin: Implications for hydrocarbon generation of suberinite (Organic Geochemistry, 2012)
The organic maceral suberinite is widely believed to be a contributor to immature or low mature oils with Ro < 0.5% in some coal and terrigenous sequences. However, its evolution of hydrocarbon generation, especially in the relatively high maturation stage of Ro > 0.5%, has not been sufﬁciently characterized. This issue was addressed herein using periderm cork tissues of the modern angiosperm Quercus suber (suberin), which is a possible bio-precursor of suberinite, in artiﬁcial bacterial degradation and hydrous pyrolysis experiments. Integrated studies were conducted, including analyses on the compositions of hydrocarbon yields and the content variations that were generated during the experiments, gas chromatography (GC) analyses of generated oils and spectral ﬂuorescence observations, and Rock-Eval and Fourier Transform Infrared (FTIR) microspectroscopic studies on solid residues. Analytical results indicate that suberin and suberinite have long and complex hydrocarbon generation histories. In general, the hydrocarbon that is generated during bacterial degradation is predominantly gas and present in relatively limited amounts, while the oils mainly are generated during hydrous pyrolysis. Furthermore, the oil generation has two peaks that correspond to Ro of approximately 0.35–0.50% and 0.80–1.10%. In composition, the early generated oil mainly consists of long chain waxy and oxygen containing compounds, while the late generated oil is relatively enriched in aromatic compounds. These features can be ascribed to the chemical nature (e.g., composition and structure) of suberin. It is a type of insoluble and high molecular weight polyester compound that contains large quantities of long chain structure dicarboxylic acids and alcohols. Consequently, the deoxygenization of these compounds can take place under relatively low thermodynamic conditions, generating liquid oil that is dominated by a long chain structure and oxygen-containing waxy compounds. In contrast, the degradation of the phenolic compounds results in the second oil generation peak. Therefore, suberinite has a two stage and relatively long oil generation history and is a good bio-precursor for coal-derived oil generation.